(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The game of cricket is known for its physical demands and players are susceptible to various types of injuries. This study aims to explore the types of injuries sustained by male cricketers. The sample comprised of 100 male cricketers from Chandigarh. Data were collected for 3 months using a self-report questionnaire. Results showed that the most common injury types among cricketers are abrasions at the upper and lower limbs followed by a strain more prone at the lower back followed by bruises mostly at the knee and ankle. These findings highlight the need for injury prevention strategies for cricketers.